1977
DOI: 10.1037/h0077361
|View full text |Cite
|
Sign up to set email alerts
|

Communication among hamsters by high-frequency acoustic signals: II. Determinants of calling by females and males.

Abstract: Basal rates of high-frequency vocalization by estrous female hamsters exceeded those typical of nonestrous females. Even higher rates of calling by estrous females were provoked by male odors (male shavings or anesthetized males). This suggests that cues which normally indicate a male's proximity can increase the rate of high-frequency calls by an estrous female. These findings are consistent with a view of female "ultrasounds" as sexual advertisements which indicate the locations, sexual receptivity, and rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

1979
1979
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(43 citation statements)
references
References 12 publications
2
41
0
Order By: Relevance
“…In contrast, other hamster species and more distantly related rodents do vocalize to conspecific odours. For example, Syrian hamsters, Mesocricetus auratus, and house mice, Mus musculus domesticus, vocalize upon exposure to opposite-sex cues (Floody, Pfaff, & Lewis, 1977;Nyby et al, 1981). The necessity of another Siberian hamster's physical presence for eliciting vocal behaviour suggests that the vocalizations we documented are likely involved in mediating direct social interactions between same-sex hamsters.…”
Section: Social Function Of Siberian Hamster Vocalizationsmentioning
confidence: 78%
“…In contrast, other hamster species and more distantly related rodents do vocalize to conspecific odours. For example, Syrian hamsters, Mesocricetus auratus, and house mice, Mus musculus domesticus, vocalize upon exposure to opposite-sex cues (Floody, Pfaff, & Lewis, 1977;Nyby et al, 1981). The necessity of another Siberian hamster's physical presence for eliciting vocal behaviour suggests that the vocalizations we documented are likely involved in mediating direct social interactions between same-sex hamsters.…”
Section: Social Function Of Siberian Hamster Vocalizationsmentioning
confidence: 78%
“…Similar vocalizations were recorded in C. pearsoni during male-female sexual encounters, and a sexual function was also proposed for these calls (Francescoli 1999). It has also been shown that female hamsters emitted ultrasound vocalizations during heterosexual encounters and these calls seemed to indicate sexual receptivity of the vocalizing females (Floody et al 1977). More studies, including direct assessment of females' reproductive state, are needed to test the hypothesis about functions of C. talarum female mating vocalizations.…”
Section: Discussionmentioning
confidence: 96%
“…Receptive female hamsters provide many potentially important stimuli to males in addition to vaginal odors [16]. In mating tests these cues might attract and direct the males' investigatory behavior and thereby help to achieve close contact between animals.…”
Section: Discussionmentioning
confidence: 99%